EFEKTIVITAS KEBIJAKAN PERCEPATAN SERTIFIKASI TANAH MELALUI PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) DI KABUPATEN TAKALAR - Nasir, Nasir (STISIP Widyapuri Mandiri Sukabumi, 2025)
The Complete Systematic Land Registration Program (PTSL) is a national policy that aims to accelerate the land certification process for all Indonesian people in order to create legal certainty over land ownership. However, in its implementation, this program still faces various obstacles, especially in the regions. This study aims to analyze the effectiveness of the policy to accelerate land certification through the PTSL program in Takalar Regency. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The research subjects consisted of officers of the National Land Agency (BPN), village officials, and PTSL beneficiary communities. Data analysis was carried out using the Miles and Huberman model, including data reduction, data presentation, and conclusion drawn. The results of the study show that the PTSL policy in Takalar Regency is quite effective, characterized by the increase in the number of certified land and the legal benefits felt by the community. However, several obstacles are still found, such as lack of socialization, limited implementing resources, and weak coordination between related agencies. The success of the program is highly dependent on the support and participation of the village government as well as the readiness of the community as service recipients. This research contributes to strengthening the study of public policy implementation, especially in the land sector, and can be a practical input for the government in developing policy strategies that are more effective, participatory, and adaptive to the needs of the community.